Learning from prior innovative project experience: A study of entrepreneurs developing Google apps - SAMIMI, Mehdi (Institutional Knowledge at Singapore Management University, 2019)
This paper investigates whether and how learning in highly-dynamic entrepreneurial ecosystems is affected by time. This study focuses on entrepreneurs who create and launch software applications in digital product markets, such as the Google app store. Such highly dynamic and competitive settings imply substantial challenges for learning from prior projects related to knowledge retention and obsolescence. This study builds on prior research by Fan and Geng (2012), who investigated similar learning patterns in the context of early Facebook apps from 2007 to 2008. The current study supports the surprisingly narrow time window during which entrepreneurs can benefit from prior experiences. Our findings support a positive time-moderated inverse U-shaped effect of prior software project experience on the performance of future projects. Prior project experiences in the intermediate past have much stronger positive effects compared to experiences from very recent prior projects or more distant projects. Consequently, our study provides additional supportive evidence that time plays a crucial role in learning from own experience in high-dynamic and innovative project settings. This study contributes to theories of innovation and organizational learning that have started to account for the impact of time.